JIBE 2020
DOI: 10.51240/jibe.2021.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Customer Satisfaction and Service Quality in Private Banks of India

Abstract: This study attempts to analyze the extent of service quality and customer loyalty in private banks. For any bank to grow and develop sustainably, they need to ensure their customer’s satisfaction in which service quality plays a decisive role. Satisfied customers, similarly, provoke customer’s loyalty towards their banks that can then enhance the profitability of Banks. With the help of the SERVQUAL Model, the study also traces various factors considered when measuring customer satisfaction. The primary data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Also, Luo and Bhattacharya (2006) confirmed that the diversity of products is one of the critical points in B2C retailers' success. Mishra (2007) declared adherence, amiability, diligence, value for money and service orientation as the five major dimensions influencing on customers' satisfaction in the electronic banking industry. Yen and Lu (2008) approved that communication is one ways for e-retailers to understand the customer's ideas about their performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, Luo and Bhattacharya (2006) confirmed that the diversity of products is one of the critical points in B2C retailers' success. Mishra (2007) declared adherence, amiability, diligence, value for money and service orientation as the five major dimensions influencing on customers' satisfaction in the electronic banking industry. Yen and Lu (2008) approved that communication is one ways for e-retailers to understand the customer's ideas about their performance.…”
Section: Literature Reviewmentioning
confidence: 99%